2021
DOI: 10.1002/er.6725
|View full text |Cite
|
Sign up to set email alerts
|

High photoelectrochemical performance of a p‐type reduced grapheneoxide‐copperoxide/Cu foil (rGO‐CuO/Cu) photoelectrode prepared by a one‐pot hydrothermal method

Abstract: Toward solar-to-hydrogen generation, it is required to assembling an efficient photoelectrode in the solar energy conversion system. The preparation of rGO-CuO/Cu photoelectrode via a facile one-pot hydrothermal approach is reported. Here, we present the physicochemical and performance of rGO-CuO/Cu photoelectrode in different hydrothermal reaction time. The XRD, XPS, HRTEM, FESEM, and Raman analysis authenticate the formation of rGO-CuO/Cu composites. The photoelectrochemical properties measurement (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Graphene, graphene oxide and reduced graphene oxide attracted large interest as a support for many photocatalyst, including CuO and Cu 2 O. Such materials have been summarized in numerous review articles [ 173 , 198 , 199 ]. First of all, combination of copper oxide materials with a highly conductive graphene framework is an attractive approach to assemble efficient photocathodes for solar fuel generation.…”
Section: Copper Oxide Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene, graphene oxide and reduced graphene oxide attracted large interest as a support for many photocatalyst, including CuO and Cu 2 O. Such materials have been summarized in numerous review articles [ 173 , 198 , 199 ]. First of all, combination of copper oxide materials with a highly conductive graphene framework is an attractive approach to assemble efficient photocathodes for solar fuel generation.…”
Section: Copper Oxide Based Materialsmentioning
confidence: 99%
“…The presence of Cu 2 O nanograins on rGO sheets can successfully ameliorate the agglomeration issue between layers while, thanks to the improved electrical conductivity, photogenerated electrons from the CB of copper oxide can be transferred instantly via rGO sheets leading to a decrease of the unfavorable recombination of carriers [ 202 ]. Such promising effects resulted in numerous example of photocatalytic and photoelectrochemical application of copper oxide/rGO: Cu 2 O/rGO and CuO/rGO as visible-light active catalysts of CO 2 photoreduction to methanol [ 203 , 204 ], Cu 2 O/rGO towards photocatalytic degradation of pollutants [ 205 , 206 , 207 ] and Cu 2 O/RGO and CuO/RGO nanocomposites for photocatalytic and photoelectrochemical H 2 evolution [ 198 , 199 , 208 ].…”
Section: Copper Oxide Based Materialsmentioning
confidence: 99%
“…Photoelectrochemical (PEC) water splitting is a promising strategy for transforming sunlight energy into H 2 to produce clean energy with no pollution or by‐products 1,10,11 . Since its discovery in the early 1970s by Honda and Fujishima for the photo‐assisted electrochemical water oxidation of n‐type TiO 2 single‐crystal electrodes, 12 PEC water splitting on various semiconducting materials has been widely studied to attain sustainable H 2 energy production and cost‐effective commercialization 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The photoelectrodes were coated with bithiophene containing covalent triazine frameworks’ (CTF-BTh) thin layers via electropolymerization to obtain high stability in a corrosive media, and it was reported that the process offered corrosion-resistant photoelectrode, enabling a long-term operation with an STH efficiency of about 3.70%. Mohd Shah et al conducted a study reporting the PEC performance of a p-type (rGO-CuO/Cu) photoelectrode prepared via a hydrothermal method, where the highest photocurrent density obtained was 9.6 mA/cm 2 (vs Ag/AgCl). Kim et al investigated a surface passivation layer treatment on a quantum-dot-sensitized TiO 2 photoelectrode performing a photocurrent density of 14.43 mA/cm 2 at 0.82 V (vs RHE).…”
Section: Introductionmentioning
confidence: 99%